Application of Governmental Accounting Standards Statement (GASS) No. 07 About Fixed Asset Accounting - Melvi Fitri; Chintya Winda Natalia Butar-Butar; Cindy Yolanda (CV. AFDIFAL MAJU BERKAH, 2025)
Fixed assets that are used by the government need an accounting treatment for fixed assets. These assets can be in the form of fixed assets that are used by the government in carrying out its operational activities. The recognition of fixed assets is regulated in the Republic of Indonesia Government Regulation No. 71 of 2010 concerning Statements of Government Accounting Standards which contain the accrual basis as applicable Government Accounting Standards. This study aims to determine the extent on application of accounting for the implementation of fixed assets. The method of analysis used in this study is a descriptive method in which the purpose of each data collected is analyzed and drawn a conclusion and the type of research conducted is descriptive qualitative. The results of the study found that the process of implementation fixed assets at the North Sumatra Province, Boyolali District, Madiun District, Bitung City, and Minahasa District Financial and Asset Management Agency is in accordance with applicable regulations.